Analysis Of The Application Of Continuity Of Care To The Competence Of Midwifery Students. - Hutahaean, Nurmalina; Simanjuntak, Merrygrace; Simanjuntak, Elvis (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: Many problems still exist in maternal and child health services. The problem of low public knowledge and the improvement of students' ability in midwifery practice are the most prominent. A solution to improve the quality of service can be in the form of a continuous care approach (COC). It can also be used to teach student clinics. Objective: Evaluate the implementation of COC in 2026 to improve the ability of midwifery practice and community knowledge of Bangun Rejo students. Methods: This study used a cross-sectional approach as an analytical descriptive design. With a total sampling technique, the study population consisted of pregnant women (±30 people), postpartum mothers (±20 people), families of toddlers (±35 families), and health workers (±10 people). Research tools include competency checklists, observation sheets, and knowledge questionnaires (pretest-posttest). The data was tested with paired t-test and chi-square test. Results: This study found a significant relationship between the implementation of COC and student competence (p = 0.002) and the improvement of community knowledge (p = 0.05). In addition, the implementation of COC in the good category was 65% and student competence was 68%. Conclusion: The implementation of Continuity of Care successfully improved students' obstetric skills and their community knowledge. Keywords: Student Ability, Midwifery Practice, and Health Education